Whole blood hemostatic resuscitation in pediatric trauma: A nationwide propensity-matched analysis. Issue 4 (7th October 2021) - Anand, Tanya; Obaid, Omar; Nelson, Adam; Chehab, Mohamad; Ditillo, Michael; Hammad, Ahmad; Douglas, Molly; Bible, Letitia; Joseph, Bellal
Abstract : Supplemental digital content is available in the text. Abstract : BACKGROUND: Whole blood (WB) has shown promise in pediatric trauma resuscitation following its prominent role in the resuscitation of adult trauma patients. Although WB in children has been shown to be feasible, its effectiveness has yet to be explored. The aim of this study was to examine the outcomes of WB transfusion as an adjunct to component therapy (CT) compared with CT only as early resuscitation for pediatric trauma patients. METHODS: Children aged 1 to 17 years, who were transfused within 4 hours of presentation, were identified in the Trauma Quality Improvement Program 2017 database. Patients were stratified into those receiving WB-CT versus CT alone. Propensity score matching in a 1:2 ratio was performed based on patient demographics, injury characteristics, hemorrhage control interventions, and trauma center level. The primary outcome measure was patient transfusion requirement. Secondary outcome measures were mortality, hospital length of stay, ventilation days, and major complications. RESULTS: A total of 135 children receiving WB-CT were matched to 270 patients receiving CT only. Mean (SD) age was 12 (5) years, 66% were male, and the median Injury Severity Score was 32 (range, 20–43). A total of 51% of patients were in shock, 34% had penetrating injuries, and 41% required surgical intervention for hemorrhage control. Total blood products transfused were significantly decreased in children receiving WB, both at 4 hours (35 [22–73] vs. 48 [33–95] mL/kg; p = 0.013) and 24 hours (39 [24–97] vs. 53 [36–119] mL/kg; p < 0.001). Mortality rate at 24 hours (19.3% vs. 21.9%; p = 0.546) and in-hospital mortality (31.1% vs. 34.4%; p = 0.502) were not different. Similarly, no difference in hospital length of stay and rates of major complications was found. Patients in the WB group required significantly less ventilation days (2 [2–6] vs. 3 [2–8] days; p = 0.021). CONCLUSION: Using WB as an adjunct to CT was associated with decreased transfusion requirements and ventilation days in pediatric trauma patients. LEVEL OF EVIDENCE: Therapeutic, level III.